Micro-Mismatch Loss Analysis Based on Solar Cell IV Curve. (November 2019) - Wang, Lei; Liu, Fuguang; Zhang, Zhen; Shao, Xi; Zhu, Zengwei; Deng, Shifeng
Abstract: Solar cells are usually connected in series and parallel to meet the voltage and current requirements for application. Shadows on the surface of C-Si (crystalline silicon) solar cell modules lead to the mismatch of current and voltage between the cells, which is one of the main causes of output power loss. In this paper, an approximate calculation method based on IV curve model is introduced. The micro-mismatch is defined as the ratio of current mismatch is less than ( ISC – Im )/ ISC, usually less than 6%. According to calculation and experiment result, power losses caused by solar cells micro mismatch of Imp, Pm, Vm, FF in solar module were analyzed. The result shows that the introduced method can simulate the micro mismatch effect of solar cell application. The module power loss is not obvious, when cell matching is less than 1.5%. When the cells current mismatch is 5%, the influence of module power output is less than 1%.